Efektifitas Baby SPA terhadap Kualitas Tidur Bayi Umur 5-12 Bulan - Vera Iriani Abdullah; Haisah Haisah (Universitas Malahayati Lampung, 2022)
ABSTRACT : BABY SPA EFFECTIVENESS ON BABY SLEEP QUALITY AGE 5-12 MONTHS Background: According to WHO (2015), the global neonatal mortality rate is 19 per 1,000 live births. Meanwhile, according to the results of the Indonesian Demographic and Health Survey (IDHS) in 2017, the AKN was 15 per 1,000 live births. Sleep is a period characterized by marked changes in brain activity. However, inadequate sleep and poor sleep quality can result in several disorders in the wrong baby so that it can affect the baby's motor skills. One way or action to overcome or improve the quality of a baby's sleep is by massage, but it can also be combined with a baby spa.Objective: To analyze the effectiveness of sleep quality before and before baby spa treatment for infants aged 5-12.Method : uses a quasi-experimental research design using a one-group pretest-posttest design. The number of samples as many as 15 respondents were taken using purposive sampling technique. Data analysis using Wilcoxon statistical test.Result: The research shows that Baby Spa is Effective on Sleep Quality of Infants Age 6-12 Months, this is evidenced by the results of the Wilcoxon statistical test with a p-value of 0.001 0.05.Conclusion: Baby Spa is Effective on Sleep Quality for Babies Age 6-12 Months Keywords: Kota Sorong, Massase, Sleep Quality INTISARI : Baby Spa Effectiveness On Baby Sleep Quality Age 5-12 Months Latar belakang : Menurut WHO (2015), angka kematian neonatal global adalah 19 per 1.000 kelahiran hidup. Sedangkan menurut hasil Survei Demografi dan Kesehatan Indonesia (SDKI) tahun 2017 menunjukkan AKN sebesar 15 per 1.000 kelahiran hidup. Tidur adalah periode yang ditandai dengan perubahan nyata dalam aktivitas otak. Namun, tidur yang tidak adekuat dan kualitas tidur yang buruk dapat mengakibatkan beberapa gangguan pada bayi salah satunya dapat mempengaruhi motorik bayi. Salah satu cara atau tindakan untuk megatasi atau memperbaiki kualitas tidur bayi yaitu dengan pijatan, selain itu juga dapat dikombinasikan dengan baby spa.Tujuan : Untuk menganalisis efektifitas kualitas tidur sebelum dan sesudah dilakukan baby spa pada bayi umur 5-12.Metode penelitian ini menggunakan quasi eksperimen dengan rancangan penelitian menggunakan one-group pretest-posttest design. Jumlah sampel sebanyak 15 responden yang diambil menggunakan teknik purposive sampling. Analisis data menggunakan uji statistik Wilcoxon.Hasil : penelitian menunjukkan bahwa Baby Spa Efektif Terhadap Kualitas Tidur Bayi Umur 6-12 Bulan, hal ini dibuktikan dengan hasil uji statistik Wilcoxondengan nilai p-value 0,001 0,05.Kesimpulan : Baby Spa Efektif Terhadap Kualitas Tidur Bayi Umur 6-12 Bulan Kata Kunci: Sorong City, Pijat, Kualitas Tidur